2012
DOI: 10.1093/annhyg/mes006
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Nanosized and Microsized Titanium Dioxide and Iron Oxide Particles in Syrian Hamster Embryo Cells

Abstract: Potential differences in the toxicological properties of nanosized and non-nanosized particles have been notably pointed out for titanium dioxide (TiO(2)) particles, which are currently widely produced and used in many industrial areas. Nanoparticles of the iron oxides magnetite (Fe(3)O(4)) and hematite (Fe(2)O(3)) also have many industrial applications but their toxicological properties are less documented than those of TiO(2). In the present study, the in vitro cytotoxicity and genotoxicity of commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…These results differ from published findings on the genotoxicity of iron oxide, where no definitive genotoxic result was obtained from nanosized or micrometer-sized hematite particle exposures in Syrian hamster embryo cells. 76 Karlsson and co-workers found similar negative results when evaluating hematite and magnetite nanoparticles. 77 Certain confounders such as cell type could be involved in conflicting reports of toxicity as particle uptake can be influenced by the cell phenotype.…”
Section: Resultsmentioning
confidence: 84%
“…These results differ from published findings on the genotoxicity of iron oxide, where no definitive genotoxic result was obtained from nanosized or micrometer-sized hematite particle exposures in Syrian hamster embryo cells. 76 Karlsson and co-workers found similar negative results when evaluating hematite and magnetite nanoparticles. 77 Certain confounders such as cell type could be involved in conflicting reports of toxicity as particle uptake can be influenced by the cell phenotype.…”
Section: Resultsmentioning
confidence: 84%
“…Those results indicate that the chitosan nanoparticle was no significant cytotoxicity observed; in addition, the chitosan nanoparticle improved the cell growth and proliferation. In previous studies, it was indicated that the metal or metal oxide nanoparticles were with high cell toxicity [2224]. Unlike metal or metal oxide nanoparticles, the chitosan nanoparticle was nontoxic.…”
Section: Resultsmentioning
confidence: 99%
“…[172] treated SHE cells with 1.0 μg/cm 2 of TiO 2 particle for 12–72 h. The micronuclei assay revealed a significant increase in MN induction in SHE cells after NP treatment, whereas TiO 2 FPs did not show significant induction of MN formation. However, other investigators who used the same cell line have stated that cytotoxicity and genotoxicity induced by metal oxide NPs are not always higher than those induced by their FP counterparts (14–35 nm; 5,10, and 50 μg/cm 2 ) [173]. Lu et al .…”
Section: Introductionmentioning
confidence: 99%